Pengaruh layanan perbankan digital pada kepuasan nasabah perbankan - Lilis Susilawaty; Nicola Nicola (Universitas Kristen Maranatha, 2020)
This study aims to determine whether digital banking services affect banking customer satisfaction. In accordance with previous research contained there are six measurements of digital banking services that affect banking customer satisfaction, namely comfort, functional quality, employee customer involvement, quality of digital banking services, brand/ trust, and digital banking innovation (Mbama & Ezepue, 2018). The data analysis technique used is quantitative verification analysis. The data used are primary data where the questionnaire was distributed to respondents using digital banking services of PT Bank Central Asia, Tbk. (Bank BCA). For the hypothesis, multiple regression analysis is tested. Before testing the data instrument testing and classical assumption tests are performed. In total 136 respondents, the results of this study indicate that comfort, functional quality, quality of digital banking services, brand/ trust, employee customer involvement, and digital banking innovation significantly influence customer satisfaction performance at Bank BCA. But partially, showing comfort, the quality of digital banking services, and brand/ trust does not affect the performance of banking customer satisfaction. Whereas functional quality, employee customer involvement, and digital banking innovation influence the performance of banking customer satisfaction.